A kind of polypropylene resin and preparation method thereof

By introducing imine bonds between aldehyde and amino groups into polypropylene, a reversible crosslinking network is constructed, which solves the reprocessing and recycling problems caused by irreversibility in traditional polypropylene crosslinking technology, and realizes thermal reversible crosslinking of polypropylene and Efficient processing.

CN116410546BActive Publication Date: 2025-02-11PETROCHINA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111682009.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-02-11
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The crosslinking bonds formed by traditional polypropylene crosslinking technology are irreversible, resulting in the inability to process and recycle the crosslinked polypropylene.

Method used

The reversible crosslinking network is constructed by synthesizing propylene copolymers containing aldehyde groups and forming dynamic covalent bonds with the amino group in the coupling agent through imine bonds. The network is reversible fracture and recombinant at high temperatures to achieve thermally reversible crosslinking of polypropylene.

Benefits of technology

The reprocessing and recycling of polypropylene is realized, providing a larger processing window and better high temperature resistance, avoiding the irreversibility problem of traditional crosslinked polypropylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention discloses a polypropylene resin and a preparation method thereof. The polypropylene resin is a product having an imide bond formed by cross-linking a propylene copolymer having a structure of the following formula (I) and a coupling agent having a structure of the following formula (II). The polypropylene resin of the present invention is a material having a reversible cross-linked network structure, which satisfactorily solves the problem that traditional cross-linked polypropylene cannot be processed or recycled. The viscosity of the Vitrimer cross-linked polymer prepared by the present invention gradually decreases with increasing temperature, which provides a larger processing window for material molding and solves the problem that the dissociated cross-linked network structure is not resistant to high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polypropylene resin and a preparation method thereof, in particular to a polypropylene resin with a thermally reversible cross-linking function and a preparation method thereof. Background Art

[0002] Polypropylene (PP) cross-linking technology is one of the important means to improve the performance of PP materials. The performance of PP modified by cross-linking is greatly improved. At present, the commonly used polypropylene cross-linking methods mainly include radiation cross-linking and chemical cross-linking. Radiation cross-linking is to irradiate polypropylene products with high-energy rays to induce cross-linking. Its advantages are high production efficiency and high product cleanliness; its disadvantages are large equipment investment, complex operation and maintenance technology, and it is mainly suitable for the preparation of thin cross-linked products. Chemical cross-linking is to use chemical cross-linking agents to cross-link polymers, transforming the linear structure into a network structure. Among them, the peroxide cross-linking method uses organic peroxide as a cross-linking agent, but the quality stability of polypropylene products produced by the peroxide cross-linking method is not easy to control. However, the cross-linking bonds formed by the currently used polypropylene cross-linking technology are irreversible, which makes it impossible to reprocess cross-linked polypropylene, thus bringing about the problem of cross-linked polypropylene being difficult to recycle. Realizing the recycling of cross-linked polypropylene is a common goal pursued by scientific researchers and the industrial community. It not only has important economic benefits, but also has long-term social benefits.

[0003] In recent years, inspired by thermoplastic elastomers, people have introduced dynamic covalent bonds into traditional rubbers to prepare elastomeric materials with both reproducible processability and excellent cross-linking properties. Dynamic covalent bonds refer to covalent bonds that can achieve reversible breakage / recombination after being subjected to specific stimuli (such as heat, light, and pH). The polymer cross-linked network formed by this can achieve topological structure rearrangement under external influences, so it has the characteristics of plasticity, self-healing, and stimulus response. According to different reaction mechanisms, dynamic covalent bonds can be divided into two categories: dissociative and associative types: (1) Dissociative dynamic covalent bonds: new cross-linking points are formed by first breaking and then re-bonding, that is, the breaking of old bonds and the re-formation of new bonds are independent of each other. In this process, the cross-linking density of the material will change, and it may even completely dissolve. The reversible Diels-Alder (DA, [4+2] cycloaddition) reaction is a typical dissociative dynamic covalent bond. (2) Associative dynamic covalent bonds: The topological structure of the cross-linked network is rearranged through exchange reactions, that is, the breaking of old bonds and the formation of new bonds are carried out simultaneously, so the cross-linking density remains unchanged. This is completely different from the dissociative dynamic covalent bonds. The associative dynamic covalent bonds were first applied to glass-like polymers (vitrimer) by Leibler et al. in 2011 and have developed rapidly in recent years. Vitrimer is a cross-linked network constructed by associative dynamic covalent bonds, which exhibits processing properties similar to glass. When heated, the material can flow like a thermoplastic polymer, so it has the ability to be reshaped, reprocessed and self-repaired; more importantly, the material will not lose its network integrity under high temperature and solvent action, and its viscosity changes with temperature in accordance with the Arrhenius equation. When the temperature rises, the viscosity gradually decreases, and there will be no sudden change in viscosity during the DA reaction.

[0004] The imine bond is a classic associative dynamic covalent bond, which can be formed by dehydration condensation between an amine group and an aldehyde group. The advantage of this dynamic covalent bond is that it has good solvent resistance, can achieve self-repair and recycling without a catalyst, and is an effective way to obtain a thermally reversible structure. If this reaction is used to achieve chemical crosslinking between polypropylene molecular chains, and the chemical bond is used to undergo a reversible reaction at high temperature to de-crosslink the polypropylene, a new thermoplastic crosslinked polypropylene material can be obtained, and the crosslinked polypropylene can be recyclable. The dissociative dynamic covalent crosslinking network based on the DA reaction, although it can be processed again, has the problem of a narrow processing window caused by a sudden drop in viscosity, which increases the difficulty and cost of production. The Vitrimer crosslinked polymer to be prepared in the present invention has a viscosity that gradually decreases with increasing temperature, which provides a larger processing window for material molding, and can also solve the problem that the dissociative crosslinked network structure is not resistant to high temperatures.

[0005] Dalian University of Technology's 2020 master's thesis "Preparation of Thermally Reversible Cross-linked Polypropylene" designed and synthesized a series of functional -olefin monomers containing furan groups, and obtained polypropylene containing furan side groups through a one-step copolymerization with propylene, and used it as a raw material to undergo a thermally reversible Diels-Alder reaction with bismaleimide small molecules to obtain polypropylene with a thermally reversible cross-linked structure. This technology has the disadvantages of rapid dissociation of the cross-linked network after heating, a sudden drop in material viscosity, and a narrow material processing temperature window.

[0006] J Polym Sci, Part A: Polym Chem, 2017, 55(12): 2011-2018, discloses a recyclable polybutadiene elastomer containing dynamic imine bonds: a catalyst-free recyclable polybutadiene elastomer with dynamic imine crosslinking is prepared by crosslinking polybutadiene functionalized with amines with aldehydes. The document uses an imine exchange reaction between aldehyde groups and amine groups to prepare Vitrimer reversibly crosslinked cis-butadiene rubber; the defects of the technology or the shortcomings of the present invention are: there are a large number of double bonds available for reaction in the side groups of cis-butadiene rubber, which is easy to implement in the system, but the method is not applicable to polypropylene systems (polypropylene molecules do not contain double bonds).

[0007] Petrochemicals, 2020, 49(8), 753-758, Technical description: Reversibly cross-linked polypropylene was prepared by Diels-Alder reaction; the defects of this technology or the shortcomings of the present invention are: the cross-linked polypropylene is completely de-cross-linked after heating, resulting in a sudden drop in polymer viscosity and a narrow processing temperature window.

[0008] Compos Sci Technol, 2018, 168: 214-223, technology description: Preparation of styrene-butadiene rubber SBR / graphene composite materials based on interfacial imine bond crosslinking; defects of this technology or shortcomings relative to the present invention: There are a large number of double bonds in the side groups of styrene-butadiene rubber available for reaction for preparing composite materials, but this method cannot achieve Vitrimer reversible crosslinking of polypropylene.

[0009] Therefore, it is urgent to provide a new polypropylene resin to solve the problems existing in the prior art. Summary of the invention

[0010] The purpose of the present invention is to solve the problem that the traditional cross-linked polypropylene cannot be reprocessed and recycled, and to develop an associative thermally reversible cross-linked polypropylene resin.

[0011] To achieve the above object, the present invention provides a polypropylene resin, wherein the polypropylene resin is a product having an imide bond formed by cross-linking a propylene copolymer having a structure of the following formula (I) and a coupling agent having a structure of the following formula (II);

[0012]

[0013] Wherein, R is vinylbenzaldehyde or its derivatives, x=100-20000, y=0.005x-0.2x;

[0014]

[0015] Among them, R 1 is a straight chain alkane with 1 to 12 carbon atoms, R 2 It is a straight chain alkane with 1 to 6 carbon atoms.

[0016] The polypropylene resin disclosed in the present invention, based on 100% of the mass of the polypropylene resin, has a propylene copolymer content of 70-98wt%, preferably 85-98wt%, more preferably 92-97wt%, and a coupling agent content of 2-30wt%, preferably 2-15wt%, more preferably 3-8wt%.

[0017] The polypropylene resin disclosed in the present invention is preferably, in formula (I), x=300-10000, y=0.005x-0.05x.

[0018] The polypropylene resin disclosed in the present invention, the vinylbenzaldehyde or its derivatives include o-vinylbenzaldehyde, m-vinylbenzaldehyde, p-vinylbenzaldehyde, and derivatives obtained by adding at least one methyl group to the benzene ring of vinylbenzaldehyde. The derivative of vinylbenzaldehyde can be at least one of 3,5-dimethyl-p-vinylbenzaldehyde, 2,4-dimethyl-p-vinylbenzaldehyde, 3-methyl-p-vinylbenzaldehyde and 5-methyl-p-vinylbenzaldehyde.

[0019] In the polypropylene resin disclosed in the present invention, preferably, the vinylbenzaldehyde is p-vinylbenzaldehyde, and the structure of the propylene copolymer is:

[0020]

[0021] Among them, M 1 、M 2 Same or different, M 1 、M 2 Each is independently H or CH3.

[0022] Another object of the present invention is to provide a method for preparing the above-mentioned polypropylene resin, comprising the following steps:

[0023] (1) mixing a propylene copolymer, a coupling agent, and a thermal stabilizer to obtain a premixed raw material;

[0024] (2) Add the premixed raw materials obtained in step (1) into a reaction device and react at a temperature above 170° C.

[0025] The method for preparing the polypropylene resin disclosed in the present invention is preferably such that the reaction equipment used in the method can be any one of a single-screw extruder, a twin-screw extruder, an open mixer and an internal mixer.

[0026] In the preparation method of the polypropylene resin disclosed in the present invention, preferably, the propylene copolymer is prepared by direct copolymerization, and the propylene copolymer is prepared by polymerization reaction of a propylene polymerization catalyst, a co-catalyst, propylene, vinylbenzaldehyde or its derivatives.

[0027] Furthermore, the propylene polymerization catalyst is one of a Ziegler-Natta catalyst or a metallocene catalyst, and the cocatalyst is one of an alkyl aluminum or an alkyl aluminoxane, preferably diphenyldimethoxysilane, triethylaluminum and methylaluminoxane.

[0028] The dosage of the propylene polymerization catalyst is 0.0005-0.1wt% of the mass of propylene, and the molar dosage of the co-catalyst is 100-10000 times the molar dosage of the propylene polymerization catalyst; the dosage of the vinylbenzaldehyde or its derivative is 0.1-50wt% of the mass of propylene, preferably 1-10wt%; the reaction temperature of the polymerization reaction is -20-120°C; the reaction time is 0.1-10 hours; and the reaction pressure is 0.01-6MPa.

[0029] The invention discloses a method for preparing a polypropylene resin. The Ziegler-Natta catalyst and the metallocene catalyst are preferably a transition metal catalyst using a magnesium halide as a carrier; the transition metal is selected from at least one of titanium and vanadium; the Ziegler-Natta catalyst also contains an internal electron donor component, and the internal electron donor is selected from at least one of diethyl succinate, dibutyl adipate, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, 2,2-diisobutyl-1,3-dimethoxypropane and 9,9-di(methoxymethyl)fluorene.

[0030] The metallocene catalyst is selected from at least one of C2H4(Me4Cp)2MCl2, C2H4(Ind)2MCl2, C2H4(2,4,7-Me3-Ind)2MCl2, Me2Si(Flu)2MCl2, Me2SiCH2(Ind)2MCl2, Me2Si(2-MeInd)2MCl2, Me2Si(2,5-Me-Cp)2MCl2, Me2Si(4,7-Me2-Ind)2MCl2, and Me2Si(2-Me-4-Naph-Ind)2ZrCl2; in the above compounds, Me=methyl, Ph=phenyl, Cp=cyclopentadienyl, Ind=indenyl, Flu=fluorenyl, Naph=naphthyl, and M is selected from Ti, Zr or Hf.

[0031] In the preparation method of the polypropylene resin disclosed in the present invention, preferably, the heat stabilizer is at least one of a hindered phenol antioxidant and a phosphite antioxidant. The hindered phenol antioxidant includes but is not limited to monohydric hindered phenol and polyhydric hindered phenol, such as butylated hydroxytoluene BHT, antioxidant 1024, antioxidant 3114, antioxidant 1010, and antioxidant 1330; the phosphite antioxidant is a phosphite antioxidant, including but not limited to phenol-free phosphite antioxidant, low-phenol phosphite antioxidant, and phenol-containing phosphite antioxidant, such as antioxidant 168.

[0032] In the method for preparing the polypropylene resin disclosed in the present invention, preferably, the mass addition ratio of the propylene copolymer, the coupling agent and the heat stabilizer is 100:3-30:0.1-1.

[0033] In the method for preparing the polypropylene resin disclosed in the present invention, preferably, in step (2), the reaction temperature is 170°C to 230°C, preferably 180°C to 210°C.

[0034] The invention synthesizes polypropylene with aldehyde groups in side groups by direct copolymerization of propylene, so that Vitrimer reversibly cross-linked polypropylene can be prepared by imine exchange reaction between aldehyde groups and amine groups, thereby solving the problem that the Vitrimer reversible cross-linking reaction can only be implemented in polymers (synthetic rubbers) containing a large number of double bonds in the prior art.

[0035] The preferred technical solution for solving the problem of the present invention is to introduce aldehyde groups into the side groups of the polymer by synthesizing styrene monomers containing aldehyde groups and copolymerizing them with propylene.

[0036] Compared with the prior art, the present invention has the following advantages and effects:

[0037] (1) The polypropylene resin of the present invention is a material having a reversible cross-linked network structure: the aldehyde groups of the side groups of the propylene copolymer can react with the amino groups of the coupling agent to cross-link the polypropylene; when heated, the cross-linked bonds rearrange their network structure through a heat-stimulated associative exchange reaction, and the formation of new bonds and the breaking of old bonds proceed simultaneously, thereby giving the material thermoplasticity, allowing the material to be cross-linked during use and de-cross-linked during processing, thereby satisfactorily solving the problem that traditional cross-linked polypropylene cannot be reprocessed or recycled.

[0038] (2) Although the dissociated dynamic covalent cross-linked network represented by the DA reaction can be reprocessed, it has the problems of narrow processing window and sudden drop in viscosity, thus increasing the difficulty and cost of production. The viscosity of the Vitrimer cross-linked polymer prepared by the present invention gradually decreases with the increase of temperature, providing a larger processing window for material molding and solving the problem that the dissociated cross-linked network structure is not resistant to high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is the nuclear magnetic spectrum of the polypropylene copolymer of Example 1 to Example 4 of the present invention.

[0040] Figure 2 It is the infrared spectra of the final products of Comparative Example 1 and Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0041] The embodiments of the present invention will be described in detail below in conjunction with examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or conditions recommended by the manufacturer. Unless otherwise specified, all reagents or instruments used can be obtained commercially.

[0042] Sources of raw materials or equipment: The Ziegler-Natta catalyst systems used in the examples are all commercially available products, and the Ziegler-Natta catalyst is the CS-I type catalyst from Yingkou Xiangyang Catalyst Factory.

[0043] Comparative Example 1

[0044] In a 10L polymerization reactor, 2kg of liquid propylene and 0.1MPa of hydrogen were added, and 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum and 60mg of Ziegler-Natta catalyst (with magnesium chloride as a carrier, containing transition metal titanium and internal electron donor diethyl succinate) were added in sequence at 30°C. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain 1520g of a polymerization product.

[0045] 1000 g of the polymer product was added to a 35-type twin-screw extruder (Belong Keya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized. The product structure and properties are shown in Table 1.

[0046] Comparative Example 2

[0047] In a 10L polymerization reactor, 2kg of liquid propylene, 20g of 4-vinylbenzaldehyde, 0.1MPa of hydrogen, 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum, and 60mg of Ziegler-Natta catalyst (with magnesium chloride as a carrier, containing transition metal titanium and internal electron donor diethyl succinate) were added in sequence at 30°C, the temperature was raised to 75°C, and the reaction was carried out for 120 minutes. 1350g of polymerization product was obtained.

[0048] 1000 g of the polymer product was added to a 35-type twin-screw extruder (Belong Keya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized. The product structure and properties are shown in Table 1.

[0049] Comparative Example 3

[0050] The product obtained in Comparative Example 1 was added to a 35-type twin-screw extruder again for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the final product. The product structure and properties are shown in Table 1.

[0051] Example 1

[0052] In a 10L polymerization reactor, 2kg of liquid propylene, 20g of p-vinylbenzaldehyde, and 0.1MPa of hydrogen were added. At 30°C, 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum, and 60mg of Ziegler-Natta catalyst (with magnesium chloride as a carrier, containing transition metal titanium and internal electron donor diethyl succinate) were added in sequence. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain a polymerization product.

[0053] 970 g of the polymerization product, 30 g of coupling agent tri(2-aminoethyl)amine, and a heat stabilizer (10 g each of antioxidant 1010 and antioxidant 168) were mixed and added to a 35-type twin-screw extruder (Belongkeya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the target product.

[0054] The obtained product has a propylene copolymer content of 97 wt% and a coupling agent content of 3 wt%. The product structure and properties are shown in Table 1.

[0055] Example 2

[0056] In a 10L polymerization reactor, 2kg of liquid propylene, 50g of p-vinylbenzaldehyde, and 0.1MPa of hydrogen were added. At 30°C, 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum, and 60mg of Ziegler-Natta catalyst (with magnesium chloride as a carrier, containing transition metal titanium and internal electron donor diethyl succinate) were added in sequence. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain a polymerization product.

[0057] 940 g of the polymerization product, 60 g of the coupling agent tri(2-aminoethyl)amine, and a heat stabilizer (10 g each of antioxidant 1010 and antioxidant 168) were mixed and added to a 35-type twin-screw extruder (Belongkeya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the target product.

[0058] The obtained product has a propylene copolymer content of 94 wt% and a coupling agent content of 6 wt%. The product structure and properties are shown in Table 1.

[0059] Example 3

[0060] In a 10L polymerization reactor, 2kg of liquid propylene, 50g of p-vinylbenzaldehyde, and 0.2MPa of hydrogen were added. At 30°C, 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum, and 60mg of Ziegler-Natta catalyst (with magnesium chloride as a carrier, containing transition metal titanium and internal electron donor diethyl succinate) were added in sequence. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain a polymerization product.

[0061] 940 g of the polymerization product, 60 g of the coupling agent tri(2-aminoethyl)amine, and a heat stabilizer (10 g each of antioxidant 1010 and antioxidant 168) were mixed and added to a 35-type twin-screw extruder (Belongkeya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the target product.

[0062] The obtained product has a propylene copolymer content of 94 wt% and a coupling agent content of 6 wt%. The product structure and properties are shown in Table 1.

[0063] Example 4

[0064] In a 10L polymerization reactor, 2kg of liquid propylene, 100g of 3,5-dimethyl-p-vinylbenzaldehyde, and 0.2MPa of hydrogen were added. At 30°C, 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum, and 60mg of Ziegler-Natta catalyst (with magnesium chloride as a carrier, containing transition metal titanium and internal electron donor diethyl succinate) were added in sequence. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain a polymerization product.

[0065] 900 g of the polymerization product, 80 g of coupling agent tri(2-aminoethyl)amine, and a heat stabilizer (10 g each of antioxidant 1010 and antioxidant 168) were mixed and added to a 35-type twin-screw extruder (Belongkeya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the target product.

[0066] The obtained product has a propylene copolymer content of 92 wt% and a coupling agent content of 8 wt%. The product structure and properties are shown in Table 1.

[0067] Example 5

[0068] In a 10L polymerization reactor, 2kg of liquid propylene, 50g of m-vinylbenzaldehyde, and 0.1MPa of hydrogen were added. At 30°C, 0.076g of diphenyldimethoxysilane, 0.36g of triethylaluminum, and 60mg of Ziegler-Natta catalyst (with magnesium bromide as a carrier, containing transition metal vanadium and internal electron donor diisobutyl phthalate) were added in sequence. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain a polymerization product.

[0069] 960 g of the polymerization product, 40 g of coupling agent tri(2-aminoethyl)amine, and a heat stabilizer (10 g each of antioxidant 1010 and antioxidant 168) were mixed and added to a 35-type twin-screw extruder (Belongkeya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the target product.

[0070] The obtained product has a propylene copolymer content of 96 wt % and a coupling agent content of 4 wt %. The product structure and properties are shown in Table 1.

[0071] Example 6

[0072] In a 10L polymerization reactor, 2kg of liquid propylene, 200g of o-vinylbenzaldehyde, and 0.1MPa of hydrogen were added. At 30°C, 6mmol of methylaluminoxane and 200mg of metallocene catalyst Me2Si(2-Me-4-Naph-Ind)2ZrCl2 were added in sequence. The temperature was raised to 75°C and the reaction was carried out for 120min to obtain a polymerization product.

[0073] 700 g of the polymerization product, 300 g of the coupling agent ethylenediamine, and a heat stabilizer (10 g each of antioxidant 1010 and antioxidant 168) were mixed and added to a 35-type twin-screw extruder (Belongkeya Nanjing Machinery Co., Ltd.) for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the target product.

[0074] The obtained product has a propylene copolymer content of 70 wt% and a coupling agent content of 30 wt%. The product structure and properties are shown in Table 1.

[0075] Example 7

[0076] The product obtained in Example 5 was added to a 35-type twin-screw extruder again for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the final product. The product structure and properties are shown in Table 1.

[0077] Example 8

[0078] The product obtained in Example 7 was added to a 35-type twin-screw extruder again for melting. The melting section temperature of the extruder was 180°C, the melt conveying section temperature was 200°C, and the discharge port temperature was 180°C. The extruded product was cooled in a circulating water bath and pelletized to obtain the final product. The product structure and properties are shown in Table 1.

[0079] Table 1 Polymer structure and properties

[0080]

[0081] First, since vinylbenzaldehyde or its derivatives are added to the polymer of the present invention, a characteristic peak of aldehyde group appears at a chemical shift of 9.66-9.69 ppm in the nuclear magnetic spectrum of the obtained polymerization product, indicating that a propylene / vinylbenzaldehyde copolymer is synthesized; the aldehyde group on the vinylbenzaldehyde or its derivatives and the amino group on the added coupling agent can undergo a dehydration condensation reaction to generate an imine bond (Vitrimer reaction), and the formation of the imine bond can be achieved by Figure 2The infrared spectrum in the prepared polymer was confirmed; a cross-linked network structure was formed in the prepared polymer, which can be confirmed from the performance changes of the polymer in the examples: relative to Comparative Example 1, due to the introduction of a cross-linked structure, the elongation at break of the polymer in Example 1 was reduced from 680% to 185%, and the creep elongation was also reduced from 16.0% to 6.1%, which is a typical feature of network formation; further by increasing the content of vinylbenzaldehyde or its derivatives to increase the cross-linking density, such as in Example 2, the elongation at break and creep elongation of the material were further reduced, and at the same time, the flexural modulus and breaking strength of the material were significantly improved, which is due to the significant increase in the rigidity of the material due to the increased degree of cross-linking.

[0082] Secondly, the polypropylene resin of the present invention is a novel polypropylene resin with a reversible crosslinking function, and its reaction of generating imine bonds has dynamic reversibility, which belongs to a heat-sensitive reversible reaction, that is, the crosslinking network can be decrosslinked (through the reverse dissociation reaction mechanism of imine bonds) in the melt processing state, so that the material has thermoplasticity. The crosslinked polymer samples of all embodiments can be subjected to melt index measurement, indicating that the material has thermoplasticity. For example, by comparing the results of comparative example 1 with those of embodiment 1, embodiment 2, and embodiment 5, it can be seen that the performance of embodiments 1, 2, and 5 is significantly better than that of comparative example 1 due to the crosslinking structure, but the melt indexes of the three polymers are similar (i.e., the processing performance is similar), which indicates that the polypropylene resin of the present invention has the unique performance of forming a network by cooling and removing the network by high temperature, which is completely different from the permanent crosslinking network formed by traditional crosslinked polypropylene, thereby giving the crosslinked polymer the excellent characteristics of thermoplasticity. This realizes the repeated processing of the crosslinked polymer. In addition, it is well known that the molecular weight of polypropylene can be regulated by adjusting the amount of hydrogen added to the polymerization reaction. For example, in Examples 3 and 4, the hydrogen concentration is increased to obtain a polymerization product with a higher melt index. After the polymerization product is cross-linked, the cross-linked polypropylene obtained has a good network structure, so that the bending modulus, breaking strength, breaking elongation, and creep elongation of the material are comparable to those of Examples 1 and 2 with high molecular weight, and the material has excellent processability (high melt index) of low molecular weight polymers after melting.

[0083] Third, the cross-linked polypropylene prepared by the present invention can still maintain good performance after repeated processing: Example 7 is obtained by secondary processing of Example 5, and Example 8 is obtained by further processing of Example 7. After continuous multiple processing, the material performance is basically maintained without weakening. This is due to the thermal reversible cross-linking function of the polypropylene resin of the present invention. The cross-linked structure can still be stably restored after repeated processing; while Comparative Example 3 is obtained by secondary processing of Comparative Example 1, and the modulus and strength of the polymer are significantly reduced due to the polymer degradation caused by repeated processing.

[0084] Fourth, all samples in the embodiments of the present invention have a heat deformation temperature above 100°C, which is not only higher than that of uncrosslinked polypropylene samples, but also higher than that of reversibly crosslinked polypropylene samples prepared by dissociative DA reaction (given that the decrosslinking temperature of the well-known DA reaction is about 110°C, the heat deformation temperature of the cross-linked polypropylene is equivalent to that of ordinary polypropylene, which is lower than 100°C, and the cross-linked structure does not have heat resistance); in addition, thanks to the characteristics of the associative dynamic covalent bonds, even above the heat deformation temperature, the cross-linked polypropylene resin of the present invention still has a cross-linked structure, which makes the melt viscosity of the material decrease slowly, greatly broadening the processing temperature window and processing stability.

[0085] In summary, the polypropylene described in the present invention is a new type of polypropylene resin with reversible cross-linking function. During melt processing, it has the remarkable characteristics of high temperature (during processing) de-crosslinking and easy processing, and low temperature (after molding) cross-linking and high performance.

Claims

1. A polypropylene resin, characterized in that The polypropylene resin is a product having an imide bond formed by cross-linking a propylene copolymer having a structure of the following formula (I) and a coupling agent having a structure of the following formula (II); Formula (I), Wherein, R is vinylbenzaldehyde or its derivatives, x = 100~20000, y = 0.005x ~ 0.2x; or Formula (II), Among them, R 1 is a straight-chain alkane with 1 to 12 carbon atoms, R 2 It is a straight chain alkane with 1 to 6 carbon atoms; The polypropylene resin is calculated based on 100% of the mass of the polypropylene resin, and the content of the propylene copolymer is 70-98wt%, and the content of the coupling agent is 2-30wt%.

2. The polypropylene resin according to claim 1, characterized in that The polypropylene resin is calculated based on 100% of the mass of the polypropylene resin, and the content of the propylene copolymer is 85-98wt%, and the content of the coupling agent is 2-15wt%.

3. The polypropylene resin according to claim 2, characterized in that The polypropylene resin is calculated based on 100% of the mass of the polypropylene resin, and the content of the propylene copolymer is 92-97wt%, and the content of the coupling agent is 3-8wt%.

4. The polypropylene resin according to claim 1, characterized in that In the formula (I), x = 300~10000, y = 0.005x ~0.05x.

5. The polypropylene resin according to claim 1, characterized in that The vinylbenzaldehyde or its derivatives include o-vinylbenzaldehyde, m-vinylbenzaldehyde, p-vinylbenzaldehyde, and derivatives obtained by adding at least one methyl group to the benzene ring of vinylbenzaldehyde.

6. The polypropylene resin according to claim 5, characterized in that The vinylbenzaldehyde is p-vinylbenzaldehyde, and the structure of the propylene copolymer is: Among them, M 1 、M 2 Same or different, M 1 、M 2 Each is independently H or CH3.

7. A method for preparing the polypropylene resin according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing a propylene copolymer, a coupling agent, and a thermal stabilizer to obtain a premixed raw material; (2) Add the premixed raw material obtained in step (1) into a reaction device and react at a temperature above 170° C. to obtain a polypropylene resin.

8. The preparation method according to claim 7, characterized in that: The propylene copolymer is prepared by direct copolymerization method, by mixing a propylene polymerization catalyst, a co-catalyst, propylene, vinylbenzaldehyde or a derivative thereof and carrying out polymerization reaction.

9. The preparation method according to claim 8, characterized in that: The propylene polymerization catalyst is a Ziegler-Natta catalyst or a metallocene catalyst, and the amount used is 0.0005-0.1wt% of the mass of propylene; The co-catalyst is one of alkyl aluminum or alkyl aluminoxane, and the amount used is 100 to 10,000 times the molar amount of the propylene polymerization catalyst; The amount of the vinylbenzaldehyde or its derivatives is 0.1-50 wt % of the mass of propylene.

10. The preparation method according to claim 8, characterized in that: The cocatalysts are diphenyldimethoxysilane, triethylaluminum and methylaluminoxane.

11. The preparation method according to claim 8, characterized in that: The amount of the vinylbenzaldehyde or its derivatives is 1-10 wt % of the mass of propylene.

12. The preparation method according to claim 8, characterized in that: The reaction temperature of the polymerization reaction is -20 to 120° C., the reaction time is 0.1 to 10 hours, and the reaction pressure is 0.01 to 6 MPa.

13. The preparation method according to claim 7, characterized in that: The mass addition ratio of the propylene copolymer, the coupling agent and the heat stabilizer is 100:3-30:0.1-1.

Citation Information

Patent Citations

  • Composition comprising a cross-linked polymer network comprising pending links and cross-links exchangeable by aldehyde-imine and / or by imine-imine exchange reactions, preparation process and use

    CN108368204A

  • Process for preparation of semi-crystalline functionalized olefin copolymer

    CN111491955A